Feasibility and Performance Analysis of High-Energy-Density Hydrocarbon-Fueled Turboexpander Engine - Jin Gao; Ziyi Kang; Weiheng Sun; Youyin Wang; Junlong Zhang; Wen Bao (Aerospace, 2023)
With the in-depth research on hypersonic aerodynamics and hypersonic propulsion technology, humans are growing closer to space travel. Recent studies have shown that the pre-cooled air-turborocket (ATR) or turboexpander engines are some of the potential propulsion methods for reusable space vehicles and single stage-to-orbit (SSTO) missions because they have a high specific impulse at low Mach numbers, which can overcome the problem of the “thrust gap” in turbine-based combined-cycle (TBCC) engines. The ATR engine needs an additional oxidizing agent and the turboexpander engine usually uses hydrogen as fuel, which has low energy density and poor safety. To address this problem, this paper proposed a high-energy-density (HED) hydrocarbon-fueled turboexpander engine, and its feasibility has been proven through a simplified thermodynamic model. Through detailed thermodynamic analysis based on the energy and pressure balance, this paper analyzed the performance characteristics of the engine to evaluate its capacity to work in a wide speed range at low Mach numbers. The results show that the endothermic hydrocarbon-fueled turboexpander engine has good specific impulse in Mach 0∼4 at an equivalence ratio of 0.7∼1.3, and the turboexpander engine can be combined with the dual-mode scramjet and become an efficient acceleration method for SSTO missions and the reusable spacecraft.